2021
DOI: 10.26603/001c.29456
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Systems Approach to Human Movement after ACL Reconstruction: The Musculoskeletal System

Abstract: Several negative adaptations to the musculoskeletal system occur following anterior cruciate ligament (ACL) injury and ACL reconstruction (ACLR) such as arthrogenic muscle inhibition, decreased lower extremity muscle size, strength, power, as well as alterations to bone and cartilage. These changes have been associated with worse functional outcomes, altered biomechanics, and increased risk for re-injury and post-traumatic osteoarthritis. After ACL injury and subsequent ACLR, examination and evaluation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 140 publications
0
1
0
Order By: Relevance
“…Nagelli et al 41 reported reduced frontal-plane knee motion and increased frontal-plane hip motion during a single-leg drop landing task to be associated with lower scores on the ACL-RSI scale. Common impairments to the neurological system after an ACL injury, such as muscle inhibition, altered muscle activation patterns, decreased knee extension, and joint instability, 33 were also not investigated in the current study. Movement quality/strategies, muscle activation amplitude, and joint stability during dynamic tasks as well as knee extension deficits may, thus, be other factors that could be explored further as contributors to psychological readiness.…”
Section: Discussionmentioning
confidence: 99%
“…Nagelli et al 41 reported reduced frontal-plane knee motion and increased frontal-plane hip motion during a single-leg drop landing task to be associated with lower scores on the ACL-RSI scale. Common impairments to the neurological system after an ACL injury, such as muscle inhibition, altered muscle activation patterns, decreased knee extension, and joint instability, 33 were also not investigated in the current study. Movement quality/strategies, muscle activation amplitude, and joint stability during dynamic tasks as well as knee extension deficits may, thus, be other factors that could be explored further as contributors to psychological readiness.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of range of motion (ROM), which can affect functional activities, is one of the alterations that occur both after an injury and after surgery. 12 It is also associated with postoperative problems such as ABSTRACT Background: Anterior Cruciate Ligament (ACL) injury is a knee injury that generally occurs in individuals who are active in sports and can be the end of a career for athletes. ACL injuries usually require surgery.…”
mentioning
confidence: 99%